CAMPUR KODE PADA PODCAST THE CATCH UP CLUB DI YOUTUBE - Sutiara Mayulis; Felisya Wanna Putri; Fatmawati Fatmawati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This research is motivated by the phenomenon of code-mixing as a growing sociolinguistic trend in digital media, particularly YouTube and podcasts, which serve as interaction spaces for bilingual communities. The Catch Up Club podcast was selected as the research object because it exhibits intense code-mixing that has not been widely examined in previous studies. This study aims to describe and analyze the types of code-mixing and their usage trends within The Catch Up Club podcast on YouTube. A qualitative approach was employed, using content analysis on the speech in The Catch Up Club Episode 13, "Salam Bugar." Data were collected through the listening and note-taking technique, and then analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The results showed 84 instances of code-mixing, consisting of 78 instances of outer code-mixing (92.86%), 4 instances of inner code-mixing (4.76%), and 2 instances of mixed code-mixing (2.38%), with a dominance of English element insertions. These findings indicate that code-mixing in podcasts is a communication strategy influenced by bilingualism, the development of digital media, the social identity of the younger generation, and the need to use specific terms, while also contributing to the advancement of sociolinguistic studies regarding language use in digital media.